A Study on Preventing Node Isolation Attack in OLSR Protocol. (2016) - James, Jefin Liza; Thomas, Bino
Abstract: A mobile ad hoc network (MANET) is a wireless communication system of continuously self-configuring and infrastructure-less network of mobile devices which can move independently in any direction at any time.Routing protocols is required for message exchange in MANET. The most widely used routing protocol is OLSR (Optimized Link State Routing Protocol). It is efficient in bandwidth utilization and path calculation. But it is vulnerable to many types of attacks. In this paper, we discuss about various methods used to prevent a type of Denial of Service (DoS) attack called the node isolation attack that is capable to compromise OLSR protocol.